2013
DOI: 10.1021/bm401451m
|View full text |Cite
|
Sign up to set email alerts
|

Humidity and Multiscale Structure Govern Mechanical Properties and Deformation Modes in Films of Native Cellulose Nanofibrils

Abstract: Nanopapers formed by stiff and strong native cellulose nanofibrils are emerging as mechanically robust and sustainable materials to replace high-performance plastics or as flexible, transparent and "green" substrates for organic electronics. The mechanical properties endowed by nanofibrils crucially depend on mastering structure formation processes and on understanding interfibrillar interactions as well as deformation mechanisms in bulk. Herein, we show how different dispersion states of cellulose nanofibrils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
289
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(303 citation statements)
references
References 58 publications
11
289
2
1
Order By: Relevance
“…In the presence of water these physical bonds compete with water interactions leading to reduced direct interfibrillar hydrogen bonding. 12 It is known that water forms strong hydrogen bonds with polar solutes, such as carbohydrates. 50,51 Overall, the combined effects manifest in a loss of macroscopic mechanical properties under wet conditions as the network is only poorly connected.…”
Section: Mechanism Of Crosslinkingmentioning
confidence: 99%
“…In the presence of water these physical bonds compete with water interactions leading to reduced direct interfibrillar hydrogen bonding. 12 It is known that water forms strong hydrogen bonds with polar solutes, such as carbohydrates. 50,51 Overall, the combined effects manifest in a loss of macroscopic mechanical properties under wet conditions as the network is only poorly connected.…”
Section: Mechanism Of Crosslinkingmentioning
confidence: 99%
“…The dependence of yield stress on the degree of polymerization of the cellulose molecules and length of the nanofibres was also investigated but no clear trend was observed (Fukuzumi et al 2013;Henriksson et al 2008). The inelastic behaviour can be changed by changing humidity (Benitez et al 2013). It was reported that inelasticity is facilitated by high humidity, and it was proposed that here inelasticity is caused by inter-fibrillar debonding and possible sliding.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that inelasticity is facilitated by high humidity, and it was proposed that here inelasticity is caused by inter-fibrillar debonding and possible sliding. Inter-fibrillar hydrogen bonds can be weakened and broken by water molecules, leading to breakage of hydrogen bonds and reduced inter-fibrillar friction (Benitez et al 2013;Quero et al 2011). Robust cellulose nanopapers have been produced by hot pressing, with inelastic behaviour being more pronounced for less well pressed nanopapers (Ö sterberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the ionic interaction between anionic fibrils and the cationic polymer removed water from the gel, and systems relying on ionic interactions could be susceptible to aggregation. It is important to control the state of dispersion and aggregation of CNF by controlling the interactions between the fibrils in order to achieve high strength and stiffness in cellulose nanopapers [17]. In natural composites like wood, silk, mollusk shells or bone the interactions are nonionic, mainly van der Waals interactions and multiple hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%